Concurrent preputial calculi and penile carcinoma--a rare association. - Mohapatra, T. P. (BMJ Group, 1989)
A case of concurrent preputial calculi and carcinoma of the penis is reported. The causal relationship of both the lesions is still controversial and the possible common aetiopathogenesis of the entity is discussed.